Neolyrium gen. n., first South American genus of net-winged beetles with 10-segmented antennae (Coleoptera: Lycidae) - Kazantsev, Sergey V. (Zootaxa, 2005)
New genus Neolyrium gen. n. with 10-segmented antennae is described from South America, its two species, N. duidaense sp. n. and N. carltoni sp. n., discovered in Amazonian Venezuela and Ecuador. In spite of the apparent affinities with the tribe Lyropaeini that include all other taxa with 10-segmented antennae, Neolyrium is classified in Leptolycini. The potential relationships of the new genus are discussed.